The digital transformation of the music industry. The second decade: From download to streaming - Ulrich Dolata (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2020)
The music industry was the first media sector to be massively affected by digitization and the internet. In this paper, the strongly technology-driven transformation of the sector is first reconstructed, divided into distinguishable development phases and condensed into characteristic peculiarities of an extended socio-technical upheaval. Subsequently, the most recent change in the music market and consumption from buying to accessing music will be examined and the thesis will be pursued that the implementation of streaming gives rise to qualitatively new possibilities and patterns of a technically mediated observation of consumers, curation of music and commodification of the product. – – Die Musikindustrie war der erste Mediensektor, der in massiver Weise von Digitalisierung und Internet betroffen war. In diesem Aufsatz wird die stark technikgetriebene Transformation des Sektors zunächst historisch rekonstruiert, in unterscheidbare Entwicklungsphasen eingeteilt und darauf aufbauend zu charakteristischen Eigenheiten eines langgestreckten soziotechnischen Umbruchs verdichtet. Im Anschluss wird der jüngste Wandel des Musikmarktes und -konsums vom Kauf zum Zugang zu Musik in den Blick genommen und die These verfolgt, dass sich mit der Durchsetzung des Streamings qualitativ neue Möglichkeiten und Muster einer technisch vermittelten Beobachtung der Konsumenten, Kuratierung von Musik und Kommodifizierung des Produkts herausschälen.
Keywords: 300